Immediate interruption of sedation compared with usual sedation care in critically ill postoperative patients (SOS-Ventilation): a randomised, parallel-group clinical trial. Issue 10 (October 2017) - Chanques, Gerald; Conseil, Matthieu; Roger, Claire; Constantin, Jean-Michel; Prades, Albert; Carr, Julie; Muller, Laurent; Jung, Boris; Belafia, Fouad; Cissé, Moussa; Delay, Jean-Marc; de Jong, Audrey; et al.
Summary: Background: Avoidance of excessive sedation and subsequent prolonged mechanical ventilation in intensive care units (ICUs) is recommended, but no data are available for critically ill postoperative patients. We hypothesised that in such patients stopping sedation immediately after admission to the ICU could reduce unnecessary sedation and improve patient outcomes. Methods: We did a randomised, parallel-group, clinical trial at three ICUs in France. Stratified randomisation with minimisation (1:1 via a restricted web platform) was used to assign eligible patients (aged ≥18 years, admitted to an ICU after abdominal surgery, and expected to require at least 12 h of mechanical ventilation because of a critical illness defined by a Sequential Organ Failure Assessment score >1 for any organ, but without severe acute respiratory distress syndrome or brain injury) to usual sedation care provided according to recommended practices (control group) or to immediate interruption of sedation (intervention group). The primary outcome was the time to successful extubation (defined as the time from randomisation to the time of extubation [or tracheotomy mask] for at least 48 h). All patients who underwent randomisation (except for those who were excluded after randomisation) were included in the intention-to-treat analysis. This study is registered withClinicalTrials.gov, numberNCT01486121 . Findings: Between Dec 2, 2011, and Feb 27, 2014, 137 patients were randomly assigned to the control (n=68) or intervention groups (n=69). In the intention-to-treat analysis, time to successful extubation was significantly lower in the intervention group than in the control group (median 8 h [IQR 4–36] vs 50 h [29–93], group difference −33·6 h [95% CI −44·9 to −22·4]; p<0·0001). The adjusted hazard ratio was 5·2 (95% CI 3·1–8·8, p<0·0001). Interpretation: Immediate interruption of sedation in critically ill postoperative patients with organ dysfunction who were admitted to the ICU after abdominal surgery improved outcomes compared with usual sedation care. These findings support interruption of sedation in these patients following transfer from the operating room. Funding: Délégation à la Recherche Clinique et à l'Innovation du Groupement de Coopération Sanitaire de la Mission d'Enseignement, de Recherche, de Référence et d'Innovation (DRCI-GCS-MERRI) de Montpellier-Nîmes.